WAYS OF TEACHING A FOREIGN LANGUAGE TO STUDENTS AT DIFFERENT LEVELS - Odilov Nozimbek (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article offers illustrations and instances highlighting the significance of acquiring English language skills. It also delivers a concise summary of the challenges associated with learning English in teenagers and grown-ups. Additionally, it includes details about three successful approaches to mastering the English language.